Factors Affecting Purchase Intention 5G Smartphone in Indonesia Using the Extended TPB Approach - Fahrillah, Ahmad Ariq; Suroso, Arif Imam; Yuliati, Lilik Noor (Universitas Brawijaya, Indonesia, 2024)
In contemporary society, smartphones have evolved into essential tools, with fast internet connectivity playing a pivotal role. In Indonesia, the deployment of 5G networks, the fastest in the industry, has officially begun, though it's limited to just nine regions. Notably, between 2021 and 2022, the sales of 5G smartphones in Indonesia surged twofold. This research investigates the factors influencing the purchase intention of 5G smartphones in Indonesia. It employs the Theory of Planned Behavior (TPB) as the foundational framework and extends it with variables such as facilitating conditions and customer preferences. Customer preferences mediate the relationship between price, product features, aesthetic value, and purchase intention. Employing quantitative analysis via Structural Equation Modeling with SmartPLS 3.0, this study engaged 335 respondents from diverse regions in Indonesia. The findings indicate that attitude, subjective norm, perceived behavior control, customer preferences, and facilitating conditions significantly impact purchase intention. Product features and aesthetic value, but not price, influence customer preferences. Smartphone manufacturers can capitalize on these preferences by highlighting the unique features and aesthetic values of 5G smartphones and promoting their advantages and value for money through digital and print media. This research provides valuable insights for marketing professionals and policymakers in Indonesia's growing 5G smartphone market.